Towards a Common Vision of Climate Security in Kenya - Medina, Leonardo; Belli, Anna; Caroli, Giulia; DuttaGupta, Tanaya; Tarusarira, Joram; Schapendonk, Frans; Savelli, Adam; Wamukoya, George; Ogallo, Linda; Nying’uro, Patricia; Kinuthia, Monicah; Omware, Stephen; et al. (CGIAR FOCUS Climate Security, 2022)
The security implications of climate variability and change, commonly referred to as the climate-security nexus, have been widely discussed in both policy circles and academia. While climate is rarely the sole cause of conflict, it can exacerbate conflict risks and outcomes by affecting societies’ economic performance, amplifying patterns of marginalization and exclusion, and challenging the capacity of already strained institutions (von Uexkull & Buhaug, 2021). Because of its significant dependence on rain-fed agriculture, with high seasonal variations in the availability of water and pasture and high levels of political fragility, the Horn of Africa has often been portrayed as one of the regions more likely to suffer from climate-related political instability (Krampe et al., 2020). Kenya, in particular, has been the subject of several studies by research institutes and international organizations that explore whether and how climate change may affect peace and security in the country. While climate impacts will increasingly have destabilizing effects on societies and communities across Kenya, the question of how this is happening remains partially unaddressed. This report presents and summarizes the findings of the first ClimBeR Climate Security Workshop held in Nairobi on the 22nd and 23rd of June 2022.